Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00534-010-0342-9
|View full text |Cite
|
Sign up to set email alerts
|

A pictorial review of benign hepatocellular nodular lesions: comprehensive radiological assessment incorporating the concept of anomalous portal tract syndrome

Abstract: Background/purpose Although the pathological categorization system advocated by the International Working Party (IWP) on Terminology has been helpful in categorizing benign hepatocellular lesions, the diverse clinicopathological features of the lesions still cause confusion of diagnosis in clinical settings. Recently, an integrated disease concept termed ''anomalous portal tract syndrome'' (APTS) has been proposed as a congenital anomaly of the portal tract, being a single unifying etiological factor underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Focal liver cell lesions including HCA, HCC, focal nodular hyperplasia, and nodular regenerative hyperplasia have been reported in association with congenital absence of the portal vein, also known as congenital extrahepatic portosystemic shunt or Abernethy malformation [5–8, 2527]. It has been suggested that the decreased venous blood flow combined with an increased arterial blood flow could result in abnormal perfusion of the liver and to uneven vascular perfusion of the liver giving rise to a hyperplastic response, and to a spectrum of nodular lesion including HCA [5, 28]. A study on the complications of congenital portosystemic shunts in children has shown the presence of 13 tumors in 17 patients (76%), 4 corresponding to HCA, one transformed in HCC [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focal liver cell lesions including HCA, HCC, focal nodular hyperplasia, and nodular regenerative hyperplasia have been reported in association with congenital absence of the portal vein, also known as congenital extrahepatic portosystemic shunt or Abernethy malformation [5–8, 2527]. It has been suggested that the decreased venous blood flow combined with an increased arterial blood flow could result in abnormal perfusion of the liver and to uneven vascular perfusion of the liver giving rise to a hyperplastic response, and to a spectrum of nodular lesion including HCA [5, 28]. A study on the complications of congenital portosystemic shunts in children has shown the presence of 13 tumors in 17 patients (76%), 4 corresponding to HCA, one transformed in HCC [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the man, no liver parenchyma outside the lesion was available, but in the woman we observed similar anomalies in the portal tracts of the normal parenchyma than those described and observed in case of congenital absence of the portal vein. The concept of anomalous portal tract syndrome [28] has been proposed as a single unifying etiological factor underlying the development of the different types of liver nodules in the context of vascular abnormalities, although for HCA the mechanisms are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular nodules resulting from CEPS occur as a result of abnormal portal blood flow and are mostly cases of benign focal nodular hyperplasia (FNH) [3][4][5][6][7] that can be multifocal or massive. Although it is believed that the malignant transformation of hepatic nodules does not occur, hepatocellular adenomas (HCA) [8][9][10][11][12][13], hepatoblastomas (HB) [14][15][16][17], and hepatocellular carcinomas (HCC) [18][19][20][21][22][23][24][25] have been described in CEPS patients. If hepatocellular nodules resulting from CEPS are potentially malignant and neoplastic, surgical interventions may be indicated for patients with CEPS and hepatocellular nodules.…”
Section: Introductionmentioning
confidence: 99%
“…Nontypical cases with hepatocellular hemangiomatous lesions can also be interpreted by this concept [21]. Although this concept alone may not be sufficient to explain the etiology of many lesions including IPH and NRH, it is recommended to consider this concept when we encounter various difficult cases [22]. Recently, the original concept (fig.…”
Section: Conventional Classification and Diagnostic Criteria For Benimentioning
confidence: 99%